Effect of computerized cognitive training on mood, cognition, and serum brain-derived neurotrophic factor level in late-life depression — a pilot randomized controlled trial - Ma, Suk Ling; Tang, Katsie Tung; Lau, Niki Cheuk Ting; Chiu, Clement Lek Hin; Lin, Cuichan; Lam, Linda Chiu Wa; Lee, Allen Ting Chun (Frontiers in Psychiatry, 2024)
Background: The aim of this pilot randomized controlled trial was to test the feasibility of a computerized cognitive training targeting executive dysfunction in late-life depression and to investigate its impact on mood, cognition, and brain-derived neurotrophic factor (BDNF) levels. Methods: A total of 28 community-living Chinese individuals aged 55–75 with moderate-to-severe depression and cognitive symptoms (but without mild cognitive impairment or dementia) were recruited from a community centre in Hong Kong. Participants were randomly allocated to either the experimental (receiving computerized cognitive training) or the control group (receiving computer-based health education). Both programs lasted for one hour and were conducted twice a week for 6 weeks at the community centre. We assessed mood using the Hamilton Rating Scale for Depression (HAM-D) and Patient Health Questionaire-9 (PHQ-9), cognition using the Montreal Cognitive Assessment (MoCA), and serum BDNF levels at baseline and follow-up. We performed repeated measures analysis of variance to compare the differences in outcome changes between groups and correlation analysis to test if changes in mood and cognition correlated with changes in BDNF level. Results: Our sample had a mean age of 66.8 (SD=5.3) years, a mean HAM-D score of 19.4 (SD=7.5), and a mean PHQ-9 score of 18.0 (SD=6.3). No adverse effects were reported. Significant differences were observed between the experimental and control groups in changes in HAM-D (-8.4 vs -2.9; group difference=-5.5; p=0.01), PHQ-9 (-6.6 vs -0.6; -6.0; p<0.001), MoCA (1.4 vs -1.3; 2.7; p=0.001), and serum BDNF levels (in pg/ml; 2088.3 vs -3277.4; 5365.6; p=0.02). Additionally, changes in HAM-D, PHQ-9, and MoCA scores correlated significantly with changes in BDNF level. Conclusion: With computerized cognitive training improving mood and cognition and increasing serum BDNF levels in 6 weeks, it may serve as a safe and effective evidence-based alternative or adjuvant treatment for late-life depression.